Are the Chinese in Africa More Innovative than the Africans? Comparing Chinese and Nigerian Entrepreneurial Migrants' Cultures of Innovation - Dirk Kohnert (GIGA; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
The remarkable influx of Chinese migrant entrepreneurs in West Africa has been met with growing resistance from established African entrepreneurs. Whether the Chinese have a competitive edge over Africans because of distinctive sociocultural traits or whether the Chineseʹs supposed effectiveness is just a characteristic feature of any trading diaspora is open to question. This comparative exploratory study of Chinese and Nigerian entrepreneurial migrants in Ghana and Benin provides initial answers to these questions. Apparently, the cultural stimuli for migrant drivers of change are not restricted to inherited value systems and religions, such as a Protestant ethic or Confucianism. Rather, they are continually adapted and invented anew by transnational migration networks in a globalized world. There is no evidence of the supposed superiority of the innovative culture of Chinese entrepreneurial migrants versus that of African entrepreneurial migrants. Instead, there exist trading diasporas which have a generally enhanced innovative capacity vis-àvis local entrepreneurs, regardless of the national culture in which they are embedded. In addition, the rivalry of Chinese and Nigerian migrant entrepreneurs in African markets does not necessarily lead to the often suspected cut-throat competition. Often the actions of each group are complementary and mutual benefiting to those of the other. Under certain conditions they even contribute to poverty alleviation in the host country. – – Zusammenfassung: Sind Chinesen in Afrika innovativer als Afrikaner? Vergleichende Studie der unternehmerischen Innovationskultur chinesischer und nigerianischer Migranten: Dem bemerkenswerten Zustrom chinesischer Unternehmer in Westafrika begegnen afrikanische Unternehmer mit wachsendem Mißtrauen. Ob Chinesen wettbewerbsfähiger sind als Afrikaner, zum Beispiel wegen spezifischer soziokultureller Merkmale, oder ob ihre vermeintlich höhere Effektivität nur ein Merkmal jeder Händler-Diaspora ist, ist eine offene Frage. Eine vergleichende Studie über chinesische und nigerianische Unternehmer-Migranten in Ghana und Benin liefert erste Antworten. Augenscheinlich sind kulturelle Anreizsysteme für migrierende Triebkräfte des Wandels nicht beschränkt auf ererbte Wertesysteme oder Religionen, wie die Protestantische Ethik (Max Weber) oder den Konfuzianismus. Vielmehr werden sie kontinuierlich angepaßt und neu erfunden durch trans-nationale Migrationsnetzwerke in einer globalisierten Welt. Es gibt keine Anhaltspunkte für die behauptete Überlegenheit von Innovationskulturen chinesischer gegenüber der von afrikanischen Unternehmer-Migranten. Statt dessen hat eine Handels-Diaspora generell eine erhöhte Innovationskraft gegenüber einheimischen Unternehmern, unabhängig von der nationalen Kultur, in die sie eingebettet sind. Darüber hinaus, führt die Rivalität chinesischer und nigerianischer Unternehmer auf afrikanischen Märkten nicht notwendigerweise zu der oft behaupteten halsabschneiderischen Konkurrenz. Oft ergänzen sich die Handlungsweisen beider Gruppen zum gegenseitigen Vorteil. Unter günstigen Bedingungen trägt dieser Wettbewerb sogar zur Armutsminderung in ihrem Gastland bei. – – Résumé: Sont les Chinois en Afrique plus innovantes que les Africains? Ètudes comparatives des cultures d'innovation des migrants entrepreneuriales nigérians et chinois: L'afflux remarquable des entrepreneurs migrants chinois en Afrique de l'Ouest a été heurtée à la résistance croissante de la part des entrepreneurs africains établis. Que les premiers ont un avantage concurrentiel sur ce dernier en raison des traits culturelles distinctifs ou que la prétendue efficacité des chinois est simplement une caractéristique de tout diaspora commercial est ouvert à la question. Cette étude comparative exploratoire de migrants entrepreneuriales chinois et nigérians au Ghana et au Bénin offre des premières réponses à cette question. Apparemment, les stimuli culturels des migrants pilotes du changement ne sont pas limités à des systèmes des valeurs hérité ou à des valeurs religieuses, comme l'éthique protestante (Max Weber) ou le confucianisme. Plutôt, ils sont continuellement adaptés et inventés de nouveau par les réseaux de la migration transnationale dans un monde globalisé. Il n'y a aucune preuve de la prétendue supériorité de la culture de innovation des migrants chinois par rapport à celle des migrants africains entrepreneuriales. Plutôt, il existe des diasporas commerciaux qui ont une capacité d'innovation renforcée en générale vis-à-vis des entrepreneurs locaux, indépendamment de la culture nationale dans laquelle ils sont intégrés. En outre, la rivalité des entrepreneurs migrants chinois et nigérians dans les marchés africains ne conduit pas nécessairement à la concurrence coupe-gorge souvent soupçonnée. Souvent, les actions de chaque groupe sont complémentaires créant un bénéfice mutuel. Sous certaines conditions, cette situation peut même contribue à une réduction de la pauvreté dans le pays d'accueil.
Conference: 17th ISA World Congress, Gothenburg, Sweden, July, 11–17, 2010; Additional information: Author's version Available at SSRN: http://ssrn.com/abstract=1636250
Keywords: F22; N85; N87; O15; J61; M13; Z13; R23; 330; migration; trading diasporas; entrepreneurs; cultures of innovation; Africa; China; Nigeria; Ghana; Benin; Migrationsforschung; Innovationsdiffusion; Entrepreneurship-Ansatz; China; Subsahara-Afrika; Ghana; Nigeria; Benin